2016
DOI: 10.4103/1817-1737.172297
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial colonization and associated factors in patients with bronchiectasis

Abstract: OBJECTIVES:To evaluate the bacterial colonization and associated risk factors in patients with bronchiectasis.METHODS:A total of 121 patients followed at the Bronchiectasis Unit, between 1996 and 2013 and diagnosed as having noncystic fibrosis bronchiectasis with high resolution computed tomography or multi-slice computed tomography were included in this retrospective study. The following definition of colonization was used for study purposes: Detection of at least two isolates of an organism separated by at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 22 publications
1
20
0
1
Order By: Relevance
“…Colonization is usually described as the detection of at least two isolates of an organism separated by a certain amount of time [33]. In this specific context of end-stage chronic pulmonary disease at high risk of hospitalacquired infection and the unknown timing of transplant when listed, bronchial colonization risk is difficult to manage.…”
Section: Discussionmentioning
confidence: 99%
“…Colonization is usually described as the detection of at least two isolates of an organism separated by a certain amount of time [33]. In this specific context of end-stage chronic pulmonary disease at high risk of hospitalacquired infection and the unknown timing of transplant when listed, bronchial colonization risk is difficult to manage.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas aeruginosa and H. influenzae are the most common bacteria detected in bronchiectasis airways globally although proportions vary among the different populations [45,64]. Other bacterial genera described in bronchiectasis airways include Streptococcus, Prevotella, Veillonella and Staphylococcus [65][66][67].…”
Section: Geographic Variation In the Microbiology Of Bronchiectasis Tmentioning
confidence: 99%
“…This was a higher proportion than in our previous CF P. aeruginosa cough aerosol studies which is likely to be related to the difference in infection profile in patients with bronchiectasis and COPD compared with CF populations. Incidentally, we found two study participants with bronchiectasis who were high producers of H. influenzae cough aerosols, a common respiratory pathogen of patients with bronchiectasis and COPD . Whilst H. influenzae cross‐infection is not thought to occur in patients with bronchiectasis, it has been recently reported in a single study of patients with CF, although it is presently unclear if aerosol transmission plays a role in H. influenzae acquisition.…”
Section: Discussionmentioning
confidence: 87%
“…Incidentally, we found two study participants with bronchiectasis who were high producers of H. influenzae cough aerosols, 26 a common respiratory pathogen of patients with bronchiectasis and COPD. [36][37][38][39][40] Whilst H. influenzae cross-infection is not thought to occur in patients with bronchiectasis, 18 it has been recently reported in a single study of patients with CF, 41 although it is presently unclear if aerosol transmission plays a role in H. influenzae acquisition. Our study reported one non-expectorating participant with COPD who produced cough aerosols containing C. koseri and Achromobacter spp.…”
Section: Discussionmentioning
confidence: 99%